ASSESSMENT OF PHYSICO-CHEMICAL PARAMETERS OF GROUND WATER FROM KANYAKUMARI TO PALLAM (International Journal of Food and Nutritional Sciences, 2022)
A systematic study has been carried out to explore physico-chemical parameters of ground water from well and bore hole in four different stations (sites) Kanyakumari, Keezha manakudy, Chothavilai and Pallam in Kanyakumari District of South India. Water samples from well and bore hole in four stations were collected in different seasons & in two years and analyzed for temperature, pH, turbidity, alkalinity, hardness, salinity, fluoride, chloride, total dissolved solids, dissolved oxygen, BOD, electrical conductivity, total nitrogen, nitrate, sulphate, ammonia, phosphate, total phosphorus, sodium, potassium and oxidation & reduction potential. Comparative studies of parameters in different stations and in different seasons in different years were also carried out. The physico-chemical parameters were analyzed and the results were compared with water quality standards described by WHO. The above study is useful to know the water quality and their fitness for drinking purposes at various stations undertaken. Overall water quality was found satisfactory for drinking purpose without prior treatment.